Study on the Vibration Isolation Performance of Composite Subgrade Structure in Seasonal Frozen Regions - Leilei Han (Applied Sciences, 2020)
Silty clay modified by fly ash and crumb rubber is a kind of sustainable subgrade filler that has good freeze–thaw resistance stability, but weak vibration isolation performance. The objective of this study was to improve the vibration isolation of the modified soil and investigate the vibration isolation effect of the composite subgrade structure of extruded polystyrene(XPS) plates and the modified soil by the indoor impact test. First, the vibration isolation performance of silty clay, modified soil, and composite subgrade structure was respectively evaluated. Second, the effect of the XPS plate’s thickness and vibration intensity on the vibration performance of the composite subgrade structure were evaluated. Third, the vibration isolation performance of the test groups under the condition of freeze–thaw cycles was assessed. The results show that the vibration isolation performance of the subgrade can be effectively improved by setting XPS plates. The composite subgrade structure has a certain vibration isolation effect, especially in the vertical direction. Considering the vibration isolation performance and costs, 5 cm was the optimum XPS plate thickness. The composite subgrade structure showed a great vibration isolation performance under the condition of freeze–thaw cycles, so it is suitable for application in road subgrade in seasonal frozen regions.